Porous activated carbon spheres derived from resorcinol-formaldehyde resin with high performance for methylene blue removal - Nguyen, Ngoc-Tue; Dinh Do, Trung; Vu Dinh, Thao; Nguyen Ngoc, Linh; Nguyen Duc, Trung (Vietnam Journal of Science and Technology, 2025)
Porous carbon materials offer numerous practical uses, particularly in the field of adsorbents due to their remarkable characteristics, which include a low density, a high surface area, and strong electrical conductivity, amongst other benefits. The findings of synthesizing porous carbon materials using a resorcinol-formaldehyde polymerization reaction, a gelation process, and pore water evaporation at high temperature are shown in this study. The procedure was carried out in an atmosphere containing an inert gas. Analyses of the newly created materials included X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDX), specific surface area calculated using the BET equation, and many more. A porous carbon material with a specific surface area of 801.92 m2/g is feasibly manufactured.